1999
DOI: 10.1023/a:1006241811136
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: The unique capability of rice (Oryza sativa L.) seedlings to grow under anoxic conditions may result in part from their ability to express alpha-amylase and maintain the supply of sugar needed for energy metabolism. Previous studies have demonstrated that under aerobic conditions the Amy1 and Amy2 subfamily genes are regulated primarily by phytohormones while the Amy3 subfamily genes are induced during sugar starvation. The expression patterns for these alpha-amylase genes were considerably different in anoxic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
38
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(39 citation statements)
references
References 25 publications
1
38
0
Order By: Relevance
“…The importance of α-amylase during grain development has been previously suggested in cereal (Barrero et al , 2013; Hwang et al , 1999). However, results from this project have identified the relative importance of the specific isoform TaAMY3 and suggested the presence of an apparent control over α-amylase activity in wheat during the grain-filling process.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…The importance of α-amylase during grain development has been previously suggested in cereal (Barrero et al , 2013; Hwang et al , 1999). However, results from this project have identified the relative importance of the specific isoform TaAMY3 and suggested the presence of an apparent control over α-amylase activity in wheat during the grain-filling process.…”
Section: Discussionmentioning
confidence: 84%
“…All subfamilies in barley or rice have been demonstrated to be expressed at different grain developmental stages and in various tissues (Hwang et al , 1999). In wheat, three isoforms of α-amylase have been clearly identified, and a fourth has been suggested based on detection of expression (Barrero et al , 2013).…”
Section: Introductionmentioning
confidence: 99%
“…High α-amylase activity is also responsible for faster of starch breakdown and higher soluble sugar concentrations in germinating seeds under flooding (Ismail et al, 2009), which is presumably necessary for coleoptile growth (Guglielminetti et al, 1995;Perata et al, 1997;Hwang et al, 1999;Ismail et al, 2009;Mori et al, 2012). In fact, the sucrose and glucose contents were 1.6-and 2.0-times higher, respectively, in IR06F459 than in IR42 (Fig.…”
Section: Discussionmentioning
confidence: 97%
“…There are several reports on the relationship between seed germination and physiological processes such as α-amylase activity and starch mobilization. Starch is a major energy source for germinating seeds and α-amylases play an essential role in starch degradation under low-oxygen conditions (Guglielminetti et al, 1995;Perata et al, 1997;Hwang et al, 1999;Ismail et al, 2009). For instance, under low oxygen stress, tolerant rice genotypes germinate and grow faster, and more seedlings survive.…”
Section: Discussionmentioning
confidence: 99%
“…Two of these enzymes in particular are considered essential for carbohydrate catabolism in rice seedling germination, α-amylase for starch degradation and sucrose synthase for sucrose breakdown. Previous work has shown that RAmy3D expression can be induced in response to an O 2 deficit during early germination (Guglielminetti et al, 1995a,b; Perata et al, 1997; Hwang et al, 1998, 1999), and that expression between 24 and 72 h after germination is positively correlated with shoot growth (Ismail et al, 2009). Our data show that of the ten α-amylase encoding genes we analyzed, only RAmy3D ( LOC_Os08g36910 ) was up-regulated in the five tolerant genotypes and was barely detectable in IR64.…”
Section: Discussionmentioning
confidence: 99%